A Further Exploration of the Effects of Restoration Postscripts on Reactance. Issue 3 (27th May 2017) - Bessarabova, Elena; Miller, Claude H.; Russell, Jason
Abstract : This study examined the effectiveness of restoration of freedom postscripts at mitigating psychological reactance following recycling messages. Results of a 2 (freedom threat: high, low) × 2 (postscript: restoration, filler) plus 1 (offset no-message control) independent group experiment ( N  = 134) replicated prior findings demonstrating how freedom threats can increase reactance and subsequently reduce perceptions of message quality while increasing anger toward the message source. Furthermore, as predicted, following high-threat messages, a restoration postscript increased intentions to recycle, whereas following low-threat messages, no such differences were found.